2019
DOI: 10.1093/crocol/otz039
|View full text |Cite
|
Sign up to set email alerts
|

The Use of An EHR Patient Portal (Mychart-Epic) in Patients With Inflammatory Bowel Disease

Abstract: Introduction Inflammatory bowel disease (IBD) has a significant effect on patients’ overall quality of life (QoL). We hypothesized that an Electronic Health Record (EHR) patient portal (EPIC’s Mychart) can be utilized to improve QoL in IBD patients and increase vaccine uptake. Methods Patients were randomized to receive specific disease (INT) information and to a control arm (CTRL) that received periodic non-IBD related messa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Three studies were based on one clinical trial; two of them were RCTs with two different objectives and sample sizes (Abutaleb et al, 2018; Cross et al, 2019), and the third study evaluated the telehealth intervention qualitatively (Reich et al, 2019). The quantitative studies examined the effectiveness of the following interventions: web‐guided intervention, IBD management through an electronic health record patient portal, home tele‐management, telemedicine, short message services (SMS) for remote monitoring, tele‐monitoring using a mobile application, monitoring of fecal calprotectin (an inflammatory biomarker) using a smartphone application, nurse‐led annual telephone monitoring, a secure web‐based program for medication monitoring, videoconference clinics, a decision support tool to customize self‐management, a web‐based application for monitoring disease activity, and telemedicine virtual visits.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies were based on one clinical trial; two of them were RCTs with two different objectives and sample sizes (Abutaleb et al, 2018; Cross et al, 2019), and the third study evaluated the telehealth intervention qualitatively (Reich et al, 2019). The quantitative studies examined the effectiveness of the following interventions: web‐guided intervention, IBD management through an electronic health record patient portal, home tele‐management, telemedicine, short message services (SMS) for remote monitoring, tele‐monitoring using a mobile application, monitoring of fecal calprotectin (an inflammatory biomarker) using a smartphone application, nurse‐led annual telephone monitoring, a secure web‐based program for medication monitoring, videoconference clinics, a decision support tool to customize self‐management, a web‐based application for monitoring disease activity, and telemedicine virtual visits.…”
Section: Resultsmentioning
confidence: 99%
“…The second qualitative study (Walsh et al, 2019) also evaluated a web‐based program that remotely assessed patient‐reported outcomes. The qualitative studies used a semi‐structured questionnaire to collect data through face‐to‐face interviews (Walsh et al, 2019) and telephone interviews (Reich et al, 2019). Both studies employed thematic analysis for the data analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We attribute these data to our proactive approach to vaccinating patients with IBD managed in our practice with standard protocols to administer indicated vaccines during patient rooming, and high rates of communication of the importance of vaccination through our EMR patient portal. With 85.5% of our participants active on an online health system communication portal, they may have received immunization reminders, which has been shown to increase vaccine uptake in patients with IBD [38,39]. Uncertainty regarding who is responsible for providing necessary vaccinations, which patients require vaccination, and patient and provider misconceptions regarding safety of vaccinations in immunosuppressed patients may contribute to suboptimal immunization rates [27,40,41].…”
Section: Discussionmentioning
confidence: 99%